BHC Plant Design - Palileo, Delfin (College of Engineering, 1963)
The proposed plant manufactures benzenehexachloride, an agricultural insecticide. The main product is crude BHC, which is used in crops where its musty order is no problem. The secondary product is lindane, or 99 percent gamma-BHC, which can be used in foodcrops, as it is free of the musty odor so inherent in the crude BHC. The by-products are "waste" isomers, hydrochloric acid, and monochlorobenzene. The relative amounts produced per year is given as follows : Crude BHC 1000 tons per year, Lindane 126, Waste Isomers 2100, HCl 23700, Monochlorobenzene 1030. A plant of this size would need a total capitalization of 740,000 and will give a 31.2 percent return on the fixed capital before taxes are deducted, or 14.9 percent after taxes. The pay off time will be 3.18 years before taxes, or 6.72 years after taxes. From the break even chart, it can be seen that the total production must be increased to maintain the desired rate of return. The plant must produce 103 percent of the computed amount to maintain this rate of return.